2009
DOI: 10.1073/pnas.0812491106
|View full text |Cite
|
Sign up to set email alerts
|

Tissue plasminogen activator modulates the cellular and behavioral response to cocaine

Abstract: Cocaine exposure induces long-lasting molecular and structural adaptations in the brain. In this study, we show that tissue plasminogen activator (tPA), an extracellular protease involved in neuronal plasticity, modulates the biochemical and behavioral response to cocaine. When injected in the acute binge paradigm, cocaine enhanced tPA activity in the amygdala, which required activation of corticotropin-releasing factor type-1 (CRF-R1) receptors. Compared with WT mice, tPA؊/؊ mice injected with cocaine display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 33 publications
4
32
0
Order By: Relevance
“…On the basis of this evidence, we hypothesize that increased basal levels of dynorphin in the nucleus accumbens core may lead to altered dopaminergic signaling after drug exposure. Indeed, in our studies, cocaine-induced conditioned place preference and locomotor sensitization, as well as cocaine withdrawal-induced stress responses, are attenuated in tPA knockout mice (Maiya et al, 2009;Zhou et al, 2010b). Our work also indicates a potential involvement of glial systems in cocaine rewarding and stress responsivity.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Resposupporting
confidence: 51%
See 1 more Smart Citation
“…On the basis of this evidence, we hypothesize that increased basal levels of dynorphin in the nucleus accumbens core may lead to altered dopaminergic signaling after drug exposure. Indeed, in our studies, cocaine-induced conditioned place preference and locomotor sensitization, as well as cocaine withdrawal-induced stress responses, are attenuated in tPA knockout mice (Maiya et al, 2009;Zhou et al, 2010b). Our work also indicates a potential involvement of glial systems in cocaine rewarding and stress responsivity.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Resposupporting
confidence: 51%
“…It has been demonstrated that nucleus accumbens dialysate dopamine levels are decreased after stimulation of kappa opioid receptors (Spanagel et al, 1992;Zhang et al, 2004Zhang et al, , 2005b. In tissue plasminogen activator (tPA, endogenous microglia inhibitor) knockout mice, basal levels of dynorphin (but not kappa opioid receptor or enkephalin) mRNA are increased in the nucleus accumbens core (Maiya et al, 2009). On the basis of this evidence, we hypothesize that increased basal levels of dynorphin in the nucleus accumbens core may lead to altered dopaminergic signaling after drug exposure.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Respomentioning
confidence: 97%
“…This is consistent with observations that plasticity-restricting PNN components are reduced after heroin self-administration (Van Den Oever et al, 2010) and protein expression of reelin is increased after cocaine self-administration (Host et al, 2010). Interestingly, an increasing number of studies show that experimental manipulations that reduce ECM breakdown or elevate ECM levels interfere with addictive behavior in different animal models of addiction, including behavioral sensitization (morphine, cocaine, and methamphetamine; Maiya et al, 2009;Mizoguchi et al, 2007;Nagai et al, 2004Nagai et al, , 2005b, CPP (morphine, cocaine, amphetamine, methamphetamine, and nicotine; Brown et al, 2007;Maiya et al, 2009;Mizoguchi et al, 2007;Nagai et al, 2004Nagai et al, , 2005bNagai et al, , 2006, cocaine self-administration (Chen et al, 2013), and reinstatement of heroine seeking (Van Den Oever et al, 2010). In contrast, enhancement of synaptic plasticity by ECM breakdown facilitates extinction of the drug memory (Xue et al, 2014), providing a substrate to suppress drug-seeking urges.…”
Section: Commonalities Of Addictive Drugs On Ecmsupporting
confidence: 80%
“…Cocaine induces tPA mRNA expression in the prefrontal cortex and NAc (Hashimoto et al 1998; Bahi and Dreyer 2008). Acute “binge” cocaine enhances tPA activity in the central and medial nucleus of the Amy by a mechanism that requires activation of CRF 1 receptors (Maiya et al 2009). Further, cocaine-induced neuronal signaling and immediate early gene expression in the Amy and NAc, as well as its rewarding effects (as measured by conditioned place preference) are attenuated in tPA-deficient (tPA −/−) mice (Maiya et al 2009).…”
Section: Introductionmentioning
confidence: 99%